Regulation by territorialization: the political ecology of conservation & development territories - Bassett, T.J.; Gautier, D. (OpenEdition, 2014)
Introduction Under the banners of environmental conservation, food security, and sustainable development, a diverse group of public and private actors is busily dividing the global South into conservation and development territories at a variety of scales. Multiple goals and processes drive these spatial strategies to reconfigure resource access, control, and management. The production of territory to regulate populations and resources has a long tradition (Elden, 2013; Sack, 1986; Scott, 199...